Urinary isotopic analysis in the UK Armed Forces: no evidence of depleted uranium absorption in combat and other personnel in Iraq. Issue 12 (3rd July 2007) - Bland, D; Rona, R; Coggon, David; Anderson, J; Greenberg, N; Hull, L; Wessely, S
Abstract : Objectives: To assess the distribution and risk factors of depleted uranium uptake in military personnel who had taken part in the invasion of Iraq in 2003. Methods: Sector field inductively coupled plasma-mass spectrometry (SF-ICP-MS) was used to determine the uranium concentration and 238 U/ 235 U isotopic ratio in spot urine samples. The authors collected urine samples from four groups identified a priori as having different potential for exposure to depleted uranium. These groups were: combat personnel (n = 199); non-combat personnel (n = 96); medical personnel (n = 22); and "clean-up" personnel (n = 24) who had been involved in the maintenance, repair or clearance of potentially contaminated vehicles in Iraq. A short questionnaire was used to ascertain individual experience of circumstances in which depleted uranium exposure might have occurred. Results: There was no statistically significant difference in the 238 U/ 235 U ratio between groups. Mean ratios by group varied from 138.0 (95% CI 137.3 to 138.7) for clean-up personnel to 138.2 (95% CI 138.0 to 138.5) for combat personnel, and were close to the ratio of 137.9 for natural uranium. The two highest individual ratios (146.9 and 147.7) were retested using more accurate, multiple collector inductively coupled plasma-mass spectrometry (MC-ICP-MS) and found to be within measurement of error of that for natural uranium. There were no significant differences in isotope ratio between participants according to self-reported circumstances of potential depleted uranium exposure. Conclusions: Based on measurements using a SF-ICP-MS apparatus, this study provides reassurance following concern for potential widespread depleted uranium uptake in the UK military. The rare occurrence of elevated ratios may reflect the limits of accuracy of the SF-ICP-MS apparatus and not a real increase from the natural proportions of the isotopes. Any uptake of depleted uranium among participants in this study sample would be very unlikely to have any implications for health.